Tomato severe rugose virus : phylogeny, phylogeography, and identification of new natural hosts - Silva, Juliana Pereira da (2021)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Fitopatologia, 2021.